IMPLEMENTASI MOTIF BATIK GEDOG PADA HUMIDIFIER DAN DIFFUSER 2IN1 - Annafi, Erinda Hayu (Sanggitarupa, 2022)
In the world of interior design, some traditional art results such as typical Indonesian batik motifs are very rarely applied to interior design elements. Even though this batik motif will be very interesting if applied to contemporary interior accessories such as humidifiers and diffusers. The way humidifiers and diffusers work is different. Humidifiers work by removing moisture to increase the humidity content of the air. While the diffuser emits steam into the air from the essential oils that are put into it. This 2in1 humidifier and diffuser is named HUDIGO (Humidifier, Diffuser, Gedog) The naming comes from the application of batik gedog on several sides of the humidifier and 2in1 diffuser. Gedog Batik originated from Tuban, East Java. The character contained in the Gedog batik motif Kijing Miring is a character of tolerance. In this motif, there are Islamic religious teachings that are adjacent to the culture of the surrounding community, namely the Gedog batik culture which comes from Javanese culture. The two cultures can coexist without losing the original culture. This application aims to apply semiotic elements to modern interior accessories. In addition, to maintain the existence of batik. Semiotic analysis uses a qualitative approach. This is because the basic assumption of semiotics is the study of signs, where in interpreting it everyone will be different. Each object has a subjective meaning, including the subject who interprets the object.